A 19.38 dBm OIP3 gm-boosted up-conversion CMOS mixer for 5–6 GHz application. (February 2017) - Huang, Wen-Hui; Huang, I-Yu; Tseng, Yu-Shan; Hsieh, Chia-Hsu; Wang, Chua-Chin
Abstract: A highly linear up-conversion mixer for 5–6 GHz wireless local area network (WLAN) applications implemented using TSMC 0.18-μm standard complementary metal oxide semiconductor (CMOS) technology is presented. The feature of the proposed mixer is based on the double-balanced Gilbert cell with current-reused technique to enhance the third-order input intercept point (IIP3). Moreover, local oscillator (LO) body grounded and gm-boosting techniques are also integrated to boost the power conversion gain (CG). The proposed up-conversion mixer demonstrates a maximum CG of 7.21 dB, a maximum IIP3 of 13.17 dBm, an output third-order input intercept point (OIP3) of 19.38 dBm, and a DC power consumption of 4 mW on silicon given a 1.1 V supply voltage. The overall chip area including radio frequency (RF) pads is 1×0.85 mm 2, where the active area is merely 0.7×0.37 mm 2 .